Metropolitan Industrial Clusters : Patterns and Processes - Chakravorty, Sanjoy; Koo, Jun; Lall, Somik V. (World Bank, Washington, DC, 2014)
Where do industries locate within a metropolitan area? Do different industrial sectors have different patterns of location/clustering? Can these patterns be understood with reference to industry characteristics? What is the geographical relationship between clusters of different types of industry? To what extent do localization economies influence the clustering process? These questions are investigated with geographically disaggregated industry location and size data from Mumbai, Kolkata, and Chennai. Chakravorty, Koo, and Lall analyze eight industrial sectors (food/beverages, textiles, leather, printing/publishing, chemicals, metals, machinery, and electrical/electronics) for evidence of global and local clustering, and distinguish between and test for co-clustering and co-location of industries. The results suggest an evolutionary model of industry location in mixed rather than specialized industrial districts. There is little evidence of localization economies from labor markets or buyer-supplier networks. The authors suggest that land use policy is the key variable influencing the intra-metropolitan spatial distribution of industry.